Bending and buckling of open section composite columns - Wan, Kirby Zhiming (2013)
This report provides details of the design, manufacturing and testing of a test rig that is used to conduct compression tests on open section composite columns. Two composite I-beams were manufactured using two C-channels and two separate beams as moulds. L930 woven carbon/epoxy prepreg layers were used as the layup to form the composite I-beam onto the mould. The mould was secured together with tape and placed into a vacuum bag, which was then placed into an autoclave to cure the prepreg layers. Both I-beams were approximately 0.6m in length with [0,90]n stacking sequence, one of which was cured with 2 prepreg layers while the other with 8 prepreg layers. Grade AA6061 aluminium plates were used to manufacture the test rigs, which were made up of two large aluminium plates and 8 aluminium blocks. The test rig was designed with two fixed blocks mounted onto the aluminium plate for guidance while two sliding blocks were used to firmly secure the I-beams in place. The I-beams were then subjected to compression tests with the test rig installed. The calculated values of critical plate and Euler buckling values were compared with the experimental buckling loads. The plate buckling equations were found to be fairly accurate in predicting the onset of buckling in the experiment. However, Euler buckling was not observed as the critical buckling load was significantly higher than the plate buckling loads. A major source of error was attributed to the use of sliding blocks to secure the I-beams onto the test rig. The blocks were not sufficiently thick enough to firmly secure the I-beam during the tests and may have resulted in the displacement of the ends of the I-beam, resulting in uneven loading and possible torsional loading of the I-beam. To address the problem, it is recommended that future experiments uses thicker blocks in the test rig to ensure a firmer fixture of the I-beam. In addition, strain gauges can also be attached onto the specimen itself to more accurately determine the onset of buckling during the compression tests.